The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1007/s12524-021-01459-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Hyperspectral Remote Sensing and Geostatistics in Spatial Prediction of Soil Organic Carbon Content

Abstract: Estimation of spatial variability of soil organic carbon (SOC) content is important for agricultural management and environmental studies. In this study, geo-spatial prediction of SOC content was conducted to evaluate and compare geostatistical techniques of ordinary kriging (OK) and cokriging (CK) with hyperspectral satellite data (Hyperion) as an auxiliary variable. The study area located in western Uttar Pradesh, India. Hyperspectral satellite-derived spectral colour indices and spectral band reflectance us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…CI and BI showed a significant contribution to SOC prediction due to their ability to capture variations in soil color, which are often indicative of SOM content and other soil properties [63,64]. The correlation between SOC and CI and BI was already highlighted in previous studies, such as Saha et al [65], which demonstrated that different spectral color indices, especially CI, are important for SOC prediction and mapping.…”
Section: Discussionmentioning
confidence: 70%
“…CI and BI showed a significant contribution to SOC prediction due to their ability to capture variations in soil color, which are often indicative of SOM content and other soil properties [63,64]. The correlation between SOC and CI and BI was already highlighted in previous studies, such as Saha et al [65], which demonstrated that different spectral color indices, especially CI, are important for SOC prediction and mapping.…”
Section: Discussionmentioning
confidence: 70%